Analisis Budaya Organisasi, Kompensasi dan Motivasi Terhadap Semangat Kerja Karyawan di Perkebuanan Melati PTPN II Perbaungan Serdang Bedagai - Halomoan Sinaga; Syaifuddin Lubis; Zahari Zein (Universitas Medan Area, 2018)
The aims of the study aims are to determine the influence of the organizational culture on the employee morale at Melati Plantation of PTPN II Perbaungan Serdang Bedagai. To determine the influence of the motivation (through organizational culture) on the employee morale and to know the influence of the organizational culture and compensation on the employee morale at Melati Plantation of PTPN II Perbaungan Serdang Bedagai.The research was carried out starting from observations to data collecting through questionnaires. The data analysis techniques used validity, reliability test and path analysis. By using the significance level of 5 % ( 0.05), with a sample of 50, it can be seen that a significant difference between organizational culture on the employee morale at Melati Plantation of PTPN II Perbaungan Serdang Bedagai. There is a significant influence between the compensation of the employee morale at Melati Plantation of PTPN II Perbaungan Serdang Bedagai. There is no significant influence of organizational culture on the employee morale through employee motivation at Melati Plantation of PTPN II Perbaungan Serdang Bedagai. There is the interplay between organizational culture and employee compensation at Melati Plantation of PTPN II Perbaungan Serdang Bedagai. Keywords : PTPN II , Teamwork and Compensation